Metonymies don’t bomb people, people bomb people - Stefanowitsch, Anatol (Yearbook of the German Cognitive Linguistics Association, 2015)
In the cognitive linguistic literature, sentences like Nixon bombed Hanoi have long been explained in terms of metonymy, either ‘referential’ (i.e. the NP Nixon metonymically refers to the bomber pilots controlled by President Nixon), or ‘predicative’ (i.e. the verb bomb metonymically refer to the ordering of the bombing). More recently, it has been suggested that such sentences may be better analyzed as slightly untypical literal instances of the transitive construction. In this paper, a corpus-based analysis of the verb bomb is presented, which shows that the usage of this verb is very different and much more heterogeneous than the constructed examples cited in the literature suggest. It is argued that this heterogeneity cannot be coherently analyzed in terms of referential or predicative metonymy. Instead, a non-metonymic account is sketched out based on a general characterization of causative transitives and verb frames from which logical subjects are selected based on salience. This account provides a unified analysis of the phenomenon that even allows us to recognize additionally the existence of referential metonymies in certain cases. The paper contributes to a growing body of research literature that takes the idea of a ‘usage- based’ cognitive linguistics seriously by attempting to test and develop analyses empirically on the basis of authentic usage data.